2021
DOI: 10.1139/gen-2021-0011
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variations of the cytoplasmic male sterility genes orf108 and orf117 in Brassica maurorum and Moricandia arvensis, and the specificity of the mRNA processing

Abstract: The mitochondrial gene <i>orf108</i> co-transcribed with <i>atp1</i> and causes cytoplasmic male sterility in <i>Brassica</i> crops, is widely distributed across wild species and genera of <i>Brassicaceae</i>. However, intraspecific variations in the presence of <i>orf108</i> have not yet been studied, and the mechanisms for the wide distribution of the gene remain unclear. We analyzed the presence and sequence variations of <i>orf108</i> … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(10 reference statements)
1
1
0
Order By: Relevance
“…identi ed interspeci c mutations in the mitochondrial orf108 between Moricandia arvensis and Brassica oxyrrhina and observed that the Rf gene of M. arvensis that cleaved the orf108-atp1 transcript was rendered ineffective by the mutations. A similar effect of such mutations in orf108 on mRNA cleavage was also observed in Brassica maurorum(Yamagishi et al 2021b). However, the Rf gene against orf108 has not yet been identi ed, and thus, the molecular relationship between orf108 and the Rf genes is still unclear.…”
supporting
confidence: 68%
“…identi ed interspeci c mutations in the mitochondrial orf108 between Moricandia arvensis and Brassica oxyrrhina and observed that the Rf gene of M. arvensis that cleaved the orf108-atp1 transcript was rendered ineffective by the mutations. A similar effect of such mutations in orf108 on mRNA cleavage was also observed in Brassica maurorum(Yamagishi et al 2021b). However, the Rf gene against orf108 has not yet been identi ed, and thus, the molecular relationship between orf108 and the Rf genes is still unclear.…”
supporting
confidence: 68%
“…Several features common to many, but not all, identified CMS-genes were drawn from the comparison of these genes (Hanson and Bentolila, 2004; Horn et al ., 2014; Chen et al ., 2017; Kitazaki et al ., 2023), and sometimes used to drive the search for mitochondrial CMS-causing genes: a chimeric sequence comprising identifiable parts of conserved mitochondrial genes and sequences of unknown origin; association and co-transcription with a conserved mitochondrial gene; expression profile modified by the action of nuclear Rf, most often at the RNA level; a predicted protein product containing hydrophobic transmembrane domain(s). While mitochondrial-CMS genes were first thought to be unique to a species or population, some were found to have evolved variants or related mitochondrial CMS genes within plant taxa, mainly in the Brassicaceae family (L’Homme et al ., 1997; Yamagishi and Terachi, 2001; Yamagishi et al ., 2021b, a ) and the rice genus (He et al ., 2020; Zhang et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%